Jemaah Islamiyah's Proliferation Strategy:Understanding Strategic Transformation and Counterterrorism Enforcement byDensus 88 Anti-Terror in Indonesia: Strategi Perluasan Jemaah Islamiyah: Memahami Transformasi Strategis dan Penegakan Hukum Kontra-Terorisme oleh Densus 88 Anti-Teror di Indonesia - Wachid Ridwan; Raihan Faliq; Muhammad Daffa Aulia Ridwan (Universitas Negeri Semarang, 2026)
Jemaah Islamiyah (JI) is suspected of employing a novel proliferation strategy, namely nonviolent struggle. This impression emerged after Para Wijayanto (Amir JI) was apprehended by Special Detachment 88 Anti-Terror Police officers in Bekasi. Following the arrest of Abu Bakar Ba'asyir by law enforcement officers, Para Wijayanto became JI’s most influential figure. He returned to Indonesia after finishing military terrorism training in Moro,, the Philippines. According to police investigation data, he is a Moro military training alumnus, which means he is involved in the JI terrorism organization's structure. In the hands of Wijayanto, JI evolved into what the Institute for Policy Analysis of Conflict (IPAC) dubbed Neo-JI in its 2017 report. This type of struggle by terrorist organizations prefers to creep in quietly, without a violent agenda, and rely solely on social and da'wah. The shift in JI's struggle strategy under Para Wijayanto's leadership was demonstrated during the mobilization of mass demonstrations against DKI Jakarta's governor in 2012. The Deputy Head of Densus 88 explained the Defending Islam 212 demonstration in Jakarta, emphasizing that the incident should not be avoided and was motivated by a desire to commit acts of terrorism after police detected signs of such a movement. The police are aware that the radical group is anti-demonstration; they only move for action. So, the police specifically observed the movements of this group, and some of their members even fled from areas outside Jakarta. This study will examine the factors and timing of JI's transition to a nonviolent struggle strategy, similar to the preaching of Islamic mass organizations. Between 2019 and early 2024, law enforcement officers conducted extensive soft power operations to combat the rise of JI's preaching movement.